The Shīʻīs in Palestine : from the medieval golden age until the present - Friedman, Yaron, (Handbook of Oriental Studies. Section 1 The Near and Middle East;, 2020)
"In The Shīʻīs in Palestine, Yaron Friedman offers a survey of the presence of Shīʻism in the region of Palestine (today: Israel) from early Islamic history until the contemporary period. It brings to light many pieces of information and interesting developments that are not widely known, in addition to the general point that, contrary to common belief, the Shīʻī community has played a significant role in the history of Palestine. The volume includes a study of Shīʻī shrines in Palestine, as well as showing the importance of these Muslim sites and holy towns in Palestine in the Shīʻī religion".